2021
DOI: 10.3892/etm.2021.10807
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of a nonsense mutation in the L1CAM gene resulting in congenital hydrocephalus: A case report and literature review

Abstract: Congenital hydrocephalus is frequently caused by mutations in the L1 cell adhesion molecule (L1CAM) gene. The purpose of the present study was to identify possible causes of fetal hydrocephalus in a Chinese family. The samples from the parents and the hydrocephalic fetus were collected. Whole-exome sequencing and in-depth mutation analysis were performed. The identified variant, c.1267C>T.(p.Q423X), is situated on exon 11 of L1CAM gene (chromosome X:153134975). The fetus was confirmed to be hemizygous for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(73 reference statements)
1
4
0
1
Order By: Relevance
“…Cases of consecutive abortions and miscarriages have been reported in in casestudies. 14,15 Likewise this study was also able to observe a significant association (p-value 0.014) of family history in 55.6% (20 cases). Out of these 9 cases exhibited fetal hydrocephalus due to consanguinity.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Cases of consecutive abortions and miscarriages have been reported in in casestudies. 14,15 Likewise this study was also able to observe a significant association (p-value 0.014) of family history in 55.6% (20 cases). Out of these 9 cases exhibited fetal hydrocephalus due to consanguinity.…”
Section: Discussionsupporting
confidence: 73%
“…16 Non-sense, missense and frameshift mutations have been observed in association with fetal X-linked hydrocephalus in male fetuses. 14,17 Authors have identified MPDZ mutation, TRIM 1, SMARCC 1, PTCH, SHH and POMT2 in association with congenital hydrocephalus in male fetuses with or without any positive family history. 18,19 In a case-control study in Ethiopia, only 2 cases of enlarged fetal ventricular system were reported to be associated with consanguinity.…”
Section: Discussionmentioning
confidence: 99%
“… 15 It has been reported that missense mutations are subdivided as “key amino acid residues” and “surface residues.” The missense mutations which affect “key amino acid residues” are located in the extracellular part of L1CAM resulting in the diminution of both homophilic and 3 heterophilic bindings and this might produce more severe neurological problems. 16 , 17 Since the variant (Tyr784Cys) presented here, located in the second Fn domain, is required for homophilic binding, it is defined as key residue mutation.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that up to 40% of cases of hydrocephalus refer to a possible genetic etiology ( Haverkamp et al, 1999 ), and over 100 genes have been described to be mutated in syndromic hydrocephalus cases ( Kousi and Katsanis, 2016 ). Thereinto, X-linked hydrocephalus comprises about 5–15% of genetic-related congenital hydrocephalus ( Haverkamp et al, 1999 ; Zhang et al, 2006 ; Adle-Biassette et al, 2013 ), and bona fide mutations have been described in four genes, that is, L1 cell adhesion molecule ( L1CAM ), sigma 2 subunit of the adapter protein 1 complex ( AP1S2 ), multiple PDZ domain proteins ( MPDZ ), and coiled-coil domain-containing protein 88c ( CCDC88C ) ( Tarpey et al, 2006 ; Al-Dosari et al, 2013 ; Shaheen et al, 2017 ; Yang et al, 2019 ; Etchegaray et al, 2020 ; Marguet et al, 2021 ; Wang et al, 2021 ). Since the phenotypes are heterogenic, there may be more genetic loci in congenital hydrocephalus.…”
Section: Human Genetic Studies Of Hydrocephalusmentioning
confidence: 99%